Analysis of Good Governance as an Earmark of Distinctive Federalism in Nigeria Federation - Amos Ojo Adedeji (Journal of Governance and Accountability Studies, 2022)
Purpose: The restructuring of Nigeria towards the path of true federalism is a clarion call for good governance in the federation. It is argued that the enhanced performance of governmental agencies in any federation is a product of good governance, which in turn leads to peace, security, and development in the living standard of the people. The main objective of this paper is to examine good governance as a catalyst of true federalism in Nigeria. Research methodology: The paper employs a qualitative methodology that heavily relies on secondary sources of data. Results: In line with the findings, Nigeria's route to true federalism is being hampered by a variety of challenges which include but are not limited to weak leadership, corruption, flawed electoral procedures, an uneven distribution of resources, and a lack of security of lives and properties. Limitations: The study covers only Nigeria and may not be appropriate to generalize the findings to other countries practicing federalism. Contributions: The study contributes to knowledge as it examines the impact of good governance as an earmark of distinctive federalism in Nigeria federation, which has not been adequately discussed in numerous works on federalism. It recommended that good governance that encompasses accountability, prudent financial management, and an improved judicial system backed up with adequate security of life and property.